(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
In this article, we provide a detailed account of the life and work of the great English poet, lexicographer and critic Samuel Johnson. Furthermore, we discuss his contribution to English literature and also we analyse his works. It analyses the structure of Johnson’s "The Lives of English Poets" and some of the author’s critical views in the work.